Airline Alliances, Antitrust Immunity, and Market Foreclosure - Bilotkach, Volodymyr; Hüschelrath, Kai (The Review of Economics and Statistics, 2013)
We examine the issue of market foreclosure by airline partnerships with antitrust immunity. Overlapping data on frequency of service and passenger volumes on nonstop transatlantic routes with information on the dynamics of airline partnerships, we find evidence consistent with the airlines operating under antitrust immunity refusing to accept connecting passengers from the outside carriers at respective hub airports. Following the antitrust immunity, airlines outside the partnership reduce their traffic to the partner airlines' hub airports by 4.1% to 11.5%. We suggest regulators should take possible market foreclosure effects into account when assessing the competitive effects of antitrust immunity for airline alliances.